Planar chiral [2.2]paracyclophanyl-based boron fluoride complexes: synthesis, crystal structure and photophysical properties. Issue 37 (24th August 2021) - Duan, Wenzeng; Ji, Honghan; Yang, Zeren; Yao, Qingxia; Huo, Yanmin; Ren, Xuerui; Zhao, Jiaojiao; Gong, Shuwen
Abstract : Facilely synthesized planar chiral [2.2]paracyclophanyl-based boron fluoride complexes (3a–3d ) with moderate quantum yields and large Stokes shifts both in solution and solid state were reported. Abstract : Planar chiral [2.2]paracyclophanyl-based boron fluoride complexes (3a–3d ) were designed and facilely synthesized. The X-ray structure study, theoretical calculations and CD spectra reveal the intense emission and planar chiral structures of these complexes. In particular, 3a–3d show moderate quantum yields and large Stokes shifts both in solution and solid state. Furthermore, the blue-shifted mechanochromic properties of 3a and 3b were both investigated in the solid state. This work is the first study on planar chiral boron monofluoride complexes within the boron fluoride complex field.